Pelestarian dan Pengembangan Seni Ajeng Sinar Pusaka pada Penyambutan Pengantin Khas Karawang - Rosikin Wikandia (LP2M ISBI Bandung, 2016)
ABSTRACT Ajeng art preservation Hamlet origin Bambu Duri, Karangpawitan. Karawang, many obstacles. Passive role of the local artist community, the lack of regeneration culture of origin, not pro-active good relations between relevant agencies as well as the entry of modern art, the art of Ajeng undeveloped and eroded extinction. Ajeng art is a kind of art that has its peculiari- ties such as art pangajeng-ngajeng (Pangwilujeng) accompanied by Soja dances that were held at the welcoming ceremony the bride or the guest of honor. Through research with qualitative descriptive approach to the socio-cultural aspects in a systematic, empirical, and cultural theory is expected to be the presentation of Ajeng art Maya art aesthetic tradition and loved young people in the conservation and development of the art of Ajeng. Keywords: Ajeng, Dance Soja ABSTRAK Pelestarian seni Ajeng asal Dusun Bambu Duri, Karang Pawitan. Kabupaten Karawang, banyak mengalami hambatan. Pasifnya peran komunitas seniman setempat, kurang adanya regenerasi budaya asal, tidak pro aktifnya hubungan baik antara dinas terkait serta masuknya kesenian modern, maka seni Ajeng tidak berkembang dan tergerus kepunahan. Seni Ajeng merupakan jenis seni yang memiliki kekhasan seperti seni pangajeng-ngajeng (Pangwilujeng) dengan diiringi tarian Soja yang biasanya dilaksanakan pada acara upacara pengantin atau penyambutan tamu kehormatan. Melalui penelitian dengan pendekatan deskriftif kualitatif pada aspek sosial budaya secara sistematis, empiris, dan teori budaya diharapkan seni Ajeng menjadi penyajian seni Ajeng yang estetik tradisi dan dicintai generasi muda dalam rangka pelestarian dan pengembangan seni Ajeng. Kata kunci: Ajeng, Tari Soja